ПРОБЛЕМИ КОНЦЕПТУАЛЬНОГО ВИЗНАЧЕННЯ СВОБОДИ ІНФОРМАЦІЇ - Шемчук, Віктор Вікторович (SUPREMANCE OF LAW, 2019)
The article reveals a variety of approaches to the understanding of the concept of freedom of information, its essential nature. Analyzed properties and the evolutionary nature of information, as well as basic substantive signs of freedom of information, based on, first, with the theoretical, filososofsko-legal and international legal doctrinal views. Highlighted features of the interpretation of freedom of information in international acts and some national legal regulations in terms of the development of civil information society.